The IL-4/STAT6/PPARγ signaling axis is driving the expansion of the RXR heterodimer cistrome, providing complex ligand responsiveness in macrophages. Issue 9 (28th February 2018) - Daniel, Bence; Nagy, Gergely; Horvath, Attila; Czimmerer, Zsolt; Cuaranta-Monroy, Ixchelt; Poliska, Szilard; Hays, Tristan T; Sauer, Sascha; Francois-Deleuze, Jean; Nagy, Laszlo
Abstract: Retinoid X receptor (RXR) is an obligate heterodimeric partner of several nuclear receptors (NRs), and as such a central component of NR signaling regulating the immune and metabolic phenotype of macrophages. Importantly, the binding motifs of RXR heterodimers are enriched in the tissue-selective open chromatin regions of resident macrophages, suggesting roles in subtype specification. Recent genome-wide studies revealed that RXR binds to thousands of sites in the genome, but the mechanistic details how the cistrome is established and serves ligand-induced transcriptional activity remained elusive. Here we show that IL-4-mediated macrophage plasticity results in a greatly extended RXR cistrome via both direct and indirect actions of the transcription factor STAT6. Activation of STAT6 leads to chromatin remodeling and RXR recruitment to de novo enhancers. In addition, STAT6 triggers a secondary transcription factor wave, including PPARγ. PPARγ appears to be indispensable for the development of RXR-bound de novo enhancers, whose activities can be modulated by the ligands of the PPARγ:RXR heterodimer conferring ligand selective cellular responses. Collectively, these data reveal the mechanisms leading to the dynamic extension of the RXR cistrome and identify the lipid-sensing enhancer sets responsible for the appearance of ligand-preferred gene signatures in alternatively polarized macrophages.